Interaksi Obat Antihipertensi Pada Pasien Hipertensi Rawat Jalan Di Puskesmas Banyumas Kabupaten Pringsewu - Sanora, Agresia; Primadiamanti, A; Angin, M Perangin (Journal of Islamic Medicine, 2022)
Background: The prevalence of people suffering from hypertension is increasing globally, it is estimated that by 2025 many people will die from hypertension .in some cases of hypertension accompanied by comorbidities, in one prescription several drugs can be taken simultaneously and can cause drug related problems that can affect the patient's therapeutic results. Objectif : This study was to determine the potential interactions of antihypertensive drugs in hypertensive patients at the Banyumas Pringsewu Public Health Center. Methods : The research used is an observational research with a cross sectional research design and data collection is done prospectively. The sample used was medical records of outpatient hypertension patients at the Banyumas Pringsewu Health Center in March-April 2022 as many as 76 patients. Sampling method using non-probability sampling technique. The data was processed using the Medscape, Drug.com application and then classified based on the severity of the interactions that occurred. Results: The results obtained are drugs The most widely used antihypertensive is the ACE-inhibitor captoprilas much as 99% and the Calcium Antagonist group, namely amlodipine as much as 1%. As for There were 69 patients or 99% of patients with the potential for interaction, of  which 6%represents minor severity, 90% is moderate severity, and 4% is grade major severity.    Conclusion: The potential for drug interactions that occur at the Banyumas Public Health Center, Pringsewu Regency, is higher or more patients experience drug interactions, namely 91%.Keyword : Hypertension, drug interactions, outpatient